CONVERSION STRATEGIES OF FINE ARTS GRADUATES' CAPITALS AMID DIGITAL CREATIVE INDUSTRY TRANSFORMATION - Aditya Eko Adrianto; Thoriq Bidar Dardiri; Risco Herlambang Puruhita; Muhamad Naufal Gibran Nawwafi (Universitas Pendidikan Ganesha, 2026)
The rapid growth of the digital creative economy, especially in art-centered cities such as Surakarta, has created both opportunities and challenges for art graduates. Many Fine Arts graduates are shifting their careers toward digital illustration and graphic design, highlighting a gap between formal art education and the needs of today’s creative industry. This study aims to examine the capital conversion strategies used by Fine Arts graduates to adapt to the digital creative industry in Surakarta. Using a qualitative approach and a case study method, this research involves six graduates of the Indonesian Institute of the Arts (ISI) Surakarta who work as illustrators or graphic designers. The study explores how they transform academic capital into industry-relevant capital through informal learning pathways. Data were collected through in-depth interviews, digital portfolio observations, and curriculum document analysis, and were analyzed thematically using Pierre Bourdieu’s theoretical framework. The findings show that the Fine Arts curriculum, which focuses mainly on conventional art practices, does not fully meet the demands of the digital market. As a result, graduates depend on self-directed learning, creative communities, and accessible technologies such as smartphones to build hybrid forms of capital. Creative communities play a key role in this process, while digital portfolios on platforms like Instagram and X have become new sources of legitimacy, gradually reducing the importance of academic credentials. This study recommends curriculum revitalization and stronger collaboration between educational institutions and creative communities to better support art graduates.